Pengembangan Aplikasi Listening Test Berbasis Android - Rokhimatul Wakhidah; Moh. Farid Maftuh; Eda Maaliah (Politeknik Negeri Batam, 2019)
Listening is one of the skills that must be possessed by learners who learn a language. Listening becomes very important skill because it supports other skills that is speaking. The skills must always be trained to improve. Listening courses are currently done by manual, which students answer on a piece of paper and lecturers check the test result manually. The research used Research and Development method. The output of research is an application that is still in the form of prototype. With this application, lecturers more easily in organizing listening test questions and facilitate scoring test results. From the results of the validation of media experts and material experts, 68.75% were obtained. From these results, the application still needs revisions. From the results of testing to students, the results obtained 92% and can be categorized into valid criteria. Research can be continued to test its use while on learning process so that it can be used as teaching material that is suitable for use in the listening courses in the following semester.